THE INFLUENCE OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) RATING AND FINANCIAL RATIOS ON SUSTAINABLE GROWTH RATE (SGR) MODERATED BY DIGITAL BANKING (DB) IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2020–2024 PERIOD - Tri Wahyuningsih; Said Kelana Asnawi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The purpose of this study is to obtain empirical evidence of the effect of Environmental Social and Governance (ESG) Rating and Financial Ratio, namely Loan to Deposit Ratio (LDR) and Non-Performing Loan (NPL) on Sustainable Growth Rate (SGR) moderated by Digital Banking (DB) in banking companies listed on the Indonesia Stock Exchange (IDX). Research data was obtained from the annual financial statements of the banking sector listed on the IDX for the 2020-2024 period. The data analysis technique used was multiple regression analysis with the help of the SPSS application. The results of the study show that ESG, NPL, and DB variables have an effect on SGR. For the LDR variable, there was no effect on the SGR of banking companies listed on the IDX during the research period. These findings suggest that banks’ sustainable growth is affected by the quality of ESG governance, credit risk management, and digital transformation. The implication of this study is that companies need to pay attention to internal and external factors that can affect the Sustainable Growth Rate (SGR).